Growth and the ageing Joneses - Walter H. Fisher; Ben J. Heijdra (Center for Economic Studies and ifo Institute (CESifo), 2008)
We incorporate Keeping-up-with-the-Joneses (KUJ) preferences into the Blanchard-Yaari (BY) framework and develop, using an AK technology, a model of balanced growth. In this context we investigate status preference, demographic, and pension policy shocks. We find that a higher degree of KUJ lowers economic growth, while, in contrast, a decrease in the fertility and mortality rates increase it. In the second part of the paper we extend the model by incorporating a Pay-as-you-go (PAYG) pension system with a statutory retirement date. This introduces a life-cycle in human wealth earnings and implies that the growth rate is higher under PAYG. We also consider the implications of an increase in the retirement date under both defined benefit and defined contribution schemes.
Keywords: D91; E21; H55; 330; Relative consumption; OLG; endogenous growth; pension reform; Gleichgewichtiges Wachstum; Overlapping Generations; Gesamtwirtschaftlicher Konsum; Umlageverfahren; Alternde Bevölkerung; Neue Wachstumstheorie; Theorie